The current status of the Sri Lanka collection : A case study in state University libraries of Sri Lanka - Sritharan, T.; Murugathas, K.; Chandrasekar, K.; Balakumaran, L. (University of Jaffna, 2022)
The national collection of a nation refers to all types of publications related to a country, and maintaining such collection in libraries to serve the purpose of docu mentation and providing access to readers is vital. Academic libraries have a role to play in developing a national collection to meet their readers’ educational and research needs. The study intended to assess the current status of the Sri Lanka col lection maintained in the university libraries of Sri Lanka and to explore the usage and challenges faced in maintaining the collection. A descriptive survey design using a self-administered questionnaire was used to collect the data from selected 15 university libraries, and collected data were analyzed using frequencies and percentages. The findings demonstrate that a separate national collection exists in 86.6% (n=13) of the university libraries of Sri Lanka. Information resources, such as books on Sri Lanka, books written by Sri Lankans, Government publications, periodicals published in Sri Lanka, theses and dissertations, palm leaf manuscripts, and collections of reputed Sri Lankan authors were available in Sri Lanka collection in more than 50% of the libraries. The study indicated that lecturers (n=13), under graduates (n=12), and postgraduates (n=12) were the major user categories of this collection. The usage of the Sri Lanka collection was measured with the responses given on a five-point Likert scale, and it showed the range between Very high (39%), High 30.5%), and Moderate (30.5%). The study described the common preservation practices adopted by the majority of the Sri Lankan university libraries. This study identified the major challenges encountered in developing and preserving the Sri Lanka collection in these libraries. The study recommends formulating a common policy, digitizing the Sri Lanka collection, improving staff strength, and providing adequate orientation and training on conservation and preservation techniques. Further, the study suggests improving the Sri Lanka collection mainly focusing on developing a distributed national collection to build up a comprehensive, digital repository of Sri Lanka collection through cooperative collection development initiatives among the state university libraries of Sri Lanka.
Keywords: National collection; Sri Lanka collection; Collection development; University libraries